The effect of phenthoate (phe) pesticide on function of pituitary gland and ovary in female of adult white rats. - M. Kadhem, Wejdan (Al-Qadisiyah Journal of Pure Science, 2017)
The present study is designed on (40) female of adult white rats, to determine the effects of phenthoate (phe) pesticide on some of function of pituitary gland and ovary, rats were divided into two groups: control group was given distilled water through oral intubations for 30 days, treated group was given 20 mg/kg of body weight of pesticide for 30 days. The results showed significant decrease (P<0.05) in the level of Follicular Stimulating Hormone (FSH), Luteinizing Hormone (LH), estrogen and progesterone in the rats treated with pesticide compared with control group. The histological results showed that rats treated with pesticide led to significant decrease (P<0.05) in diameter of ovaries and foilicles number compared with control grou